Designing Performance Management System to Increase Customer Satisfaction (Case Study at CV. Viatexindo) - Herawati, Silviana; Febriansyah, Hary (Action Research Literate, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are crucial to Indonesia's economy, particularly in West Java, where they significantly contribute to GDP and employment.  In West Java, with a population of about 49.9 million, there are over 7 million MSMEs, marking a growth of 5.83% in 2023. The Department of Cooperative and SMEs supports these businesses by managing affairs related to cooperatives, small business licenses, and development programs. The research aims to create a performance management system specifically designed for CV. Viatexindo, a textile microenterprise, in order to improve customer satisfaction through effective employee performance management. Using a combination of qualitative and quantitative approaches, the research investigates the relationship between employee performance and customer satisfaction in a microbusiness environment. The research highlights major weaknesses in company present performance management procedures through extensive analysis, which includes job analysis, the use of Management by Objectives (MBO), and feedback integration. The findings show a strong relationship between staff performance and customer complaints, emphasizing the need for a systematic performance management system. The research presents a complete methodology for incorporating customer input into performance evaluations while emphasizing continual improvement and training. The purpose is to connect staff objectives with company goals in order to decrease customer complaints and increase overall service quality. The research adds to our understanding of performance management in micro-enterprises and gives actionable information for CV. Viatexindo to adopt improvements that could lead to increased customer satisfaction and business growth.